MO678DISTRIBUTION OF PERIPHERAL BLOOD T CELL SUBTYPES IN HEMODIALYSIS PATIENTS TREATED WITH MEDIUM CUT-OFF MEMBRANES AND HIGH-FLUX MEMBRANES. (29th May 2021) - Hasbal, Nuri Baris; Sevinç, Mustafa; Yilmaz, Vuslat; Basturk, Taner; Ahbap Dal, Elbis; Sakaci, Tamer; Ozcafer, Perin Nazif; Lindholm, Bengt; Unsal, Abdulkadir
Abstract: Background and Aims: Mortality in end stage renal disease is higher than in the general population. In addition, there is also an increase in mortality that cannot be explained by known risk factors. In this context, researchers have been determining on these additional risk factors for years. Although inflammation is a proven risk factor, further studies are still needed. In this study, we aimed to investigate the effect of membranes on the distribution of T cell subgroups in peripheral blood mononuclear cells (PBMC) that play an important role in inflammation. Method: Twenty-five patients were enrolled in the study, and patients received hemodialysis treatment first with MCO membrane (MCO) for 3 months and then with high-flux membrane (HF) for another 3 months. Peripheral blood samples were taken from the patients just before the hemodialysis procedure at 0 (starting with MCO), 3rd (switching to HF) and 6th (end of study) months. PBMC's were separated by ficoll density gradient centrifugation and stored in liquid nitrogen. Frozen cells were stained with fluorescently labeled monoclonal antibodies and were utilized with flow cytometry device. Data were analyzed using FlowJo7.6.5 programs. Results: Proportions of helper T (CD3+CD4+), cytotoxic T (CD3+CD8+), and follicular helper T (CD3+CD4+ CXCR3-CXCR5+) cells were similar in both membranes. The use of MCO decreased the ratios of peripheral CD3+T (p=0.07) and Th1 (CD3+CD4+CXCR3+CCR6+) (p<0.0001) cells while increasing the ratio of NK cells (p=0.03). In addition, the shift of the immune balance towards an increase in Th17 (CD3+CD4+CXCR3-CCR6+) (p=0.005) and Th2 (CD3+CD4+CXCR3-CCR6-) (p <0.0001) cell ratios with HF. Conclusion: : The results can be interpreted as the prevention of a Th1 dominant inflammation seen with HF. Therefore, it suggests that the use of MCO may reduce T cell based inflammation in peripheral blood.